Competitive Adsorption/Desorption of CH4/CO2/N2 Mixture on Anthracite from China for ECBM Operation. (May 2017) - Zhang, Yi; Chi, Yuan; Xing, Wanli; Liu, Shuyang; Song, Yongchen
Abstract: The adsorption/desorption of CH4 /CO2 /N2 mixture was investigated at 294 K, 311 K, 333 K, and 353 K with a wide pressure range (0∼70 Bar) on anthracite from China using a High Pressure Volumetric Analyzer (HPVAII-200). When the temperature is relatively low (293 K and 311 K), as the pressure rises, the excess adsorbed amount increases and peaks before experiencing a decrease. However, when the temperature is relatively high (353 K), the excess adsorbed amount increases and plateaus among the entire pressure range in this study. The pressure corresponding to the maximum adsorbed amount is lower in the process of desorption compared with adsorption, because there exists a hysteresis between adsorption and desorption. With the increasing temperature, the excess adsorbed amount is on the decline, which is the same as pure gas. While the pressure corresponding to the maximum adsorbed amount ascends as the temperature rises, even beyond the pressure range in this study. Moreover, the excess adsorbed amount have a good linear relationship with the temperature. Furthermore, the CO2 shows the best adsorption capacity and the adsorption capacity of CH4 is greater slightly than N2 . In addition, with the increasing temperature, the competitive adsorption among CO2, CH4 and N2 is weaker.